Association of napping and night-time sleep with impaired glucose regulation, insulin resistance and glycated haemoglobin in Chinese middle-aged adults with no diabetes: a cross-sectional study. Issue 7 (23rd July 2014) - Baoying, Huang; Hongjie, Chen; Changsheng, Qiu; Peijian, Wu; Qingfei, Lin; Yinghua, Lin; Huibin, Huang; Jixing, Liang; Liantao, Li; Ling, Chen; Kaka, Tang; Zichun, Chen; et al.
Abstract : Objective: To assess associations between napping and night-time sleep duration with impaired glucose regulation, insulin resistance (IR) and glycated haemoglobin (HbA1c). Design: Cross-sectional study. Setting: Fujian Province, China, from June 2011 to January 2012. Participants: This study enrolled 9028 participants aged 40–65 years. Data of 7568 participants with no diabetes were included for analysis. Type 2 diabetes was defined applying WHO criteria. Outcome measures: Participants' daytime napping and night-time sleep duration data were collected using a standardised self-reported Chinese-language questionnaire about sleep frequency and quality. Anthropometric and laboratory parameters were also measured. IR was defined as a HOMA-IR index value >2.50. ORs and 95% CIs were derived from multivariate logistic regression models. Results: Participants (mean age 51.1±7.0 years) included 3060 males and 4508 females with average night-time sleep of 7.9 h. A higher proportion of males napped than females. After adjustment for potential confounders, ORs for HbA1c >6.0% were 1.28 and 1.26 for those napping ≤1 h and >1 h (p=0.002 and p=0.018), respectively. Statistically significant differences in IR between nappers and non-nappers were only marginal clinically. Odds for HbA1c >6.0% were significantly lower in participants with longer night-time sleep durations than in the reference group (>8 h vs 6–8 h). Odds for IR were significantly lower in participants whose night-time sleep hours deviated from the reference group (<6 h, >8 h vs 6–8 h) Conclusions: Chinese middle-aged adults with no diabetes who napped had higher HbA1c and IR; those with shorter night-time sleep durations had increased HbA1c. Night-time sleep hours that are either <6 or >8 tend to be associated with lower odds for IR. Further studies are necessary to determine the underlying clinical significance and mechanisms behind these associations.